Aspecte teoretice și practice privind contractul de credit pentru consum [Articol] - Cazacu, Valentin (USARB, 2023)
The present study analyzes the credit agreement for consumers in the light of the amendments to the law no. 202 of 12.07.2022, in force from 29.05.2022. The study focuses, in particular, on the new provisions and its impact on consumer protection, including the analysis of case law from Tribunals, Courts of Appeal and from Supreme Court.
Keywords: credit agreement; consumer; creditor; unfair terms; interest rate; late payment interest